Children and Juvenile Literature of the Third Reich as an Instrument of Nazi Identity Formation - Anna V. Dobryashkina (Studia Litterarum)
The article examines the role of children and juvenile literature of the Third Reich in the development of Nazi identity. In German culture of the 1930s, the image of childhood developed during the period of the Weimar Republic underwent dramatic changes. As the Third Reich was proclaimed “the Youth Reich” (das jugendliche Reich), childhood lost its autonomy and merged with “youth,” the key concept of the Nazi era. Youth, in turn, was more than age category; it implied a certain worldview, or a specific life position that all age groups of Nazi society had to adhere to. Children and adolescents aged 10-18 years old joined the Hitler Youth, the largest organization in the world, and became carriers of the new ideology. Literature for children and adolescents of the Third Reich significantly expanded its boundaries: now it included literary works written for adults, and also those written before 1933. “Expanded borders,” therefore, implied multiple cases of intersection between children and adult literature, interpenetration and coexistence of these literatures within the cultural ambience of the Nazi period. Despite the fact that the entire system of education and upbringing fostered indoctrination while literature was one but not the only one factor in the development of the new identity in this multilevel system, it was literature that legitimized children’s refusal to follow their personal interests and encouraged their engagement in the propagated ideological system.